What systemic racism in Canada looks like - CBC News (2020)
The police killing of George Floyd and the protests that followed have brought renewed attention to systemic racism. In Canada, some have been quick to deny its existence. But these experts say racism has been normalized within Canadian institutions. Producer: Avneet Dhillon Research: Britnei Bilhete, Alisha Parchment Production editor: Charles Fogel Graphic designer: Thomas Hall Senior producer: Roxanna Woloshyn Executive producer: Irene Thomaidis For more stories about the experiences of Black Canadians — from anti-Black racism to success stories within the Black community — check out Being Black in Canada here: https://www.cbc.ca/beingblackincanada »»» Subscribe to CBC News to watch more videos: http://bit.ly/1RreYWS Connect with CBC News Online: For breaking news, video, audio and in-depth coverage: http://bit.ly/1Z0m6iX Find CBC News on Facebook: http://bit.ly/1WjG36m Follow CBC News on Twitter: http://bit.ly/1sA5P9H For breaking news on Twitter: http://bit.ly/1WjDyks Follow CBC News on Instagram: http://bit.ly/1Z0iE7O Download the CBC News app for iOS: http://apple.co/25mpsUz Download the CBC News app for Android: http://bit.ly/1XxuozZ »»»»»»»»»»»»»»»»»» For more than 75 years, CBC News has been the source Canadians turn to, to keep them informed about their communities, their country and their world. Through regional and national programming on multiple platforms, including CBC Television, CBC News Network, CBC Radio, CBCNews.ca, mobile and on-demand, CBC News and its internationally recognized team of award-winning journalists deliver the breaking stories, the issues, the analyses and the personalities that matter to Canadians.
Keywords: amériques; approches et analyses; canada; cours; histoire et politique; pol5480; premier cycle; pédagogie; racisme; régions géographiques; systèmes d'oppressions; thématiques; violences

Le pouvoir de l’amour - EMMA (Emma, 2020)
Salut à toutes et tous, en ces temps confinés j’ai pensé vous mettre à disposition cette histoire inédite de mon tome 3 « La charge émotionnelle ». Je souhaite plein de …
Keywords: approches et analyses; bande-dessinée; care; charge mentale; discipline; discours dominant; femmes*; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; santé; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

L’intervention psychosociale artistique: les arts pour intervenir avec les individus et les groupes - Bourassa-Dansereau, Caterine; G.-Langlois, Maxime; Robert, François P. (Nouvelles pratiques sociales, 2020)
L’intervention psychosociale utilisant les arts pour intervenir avec des individus et des groupes permet d’entrer en relation avec les personnes « autrement ». L’objectif de cet article est de présenter l’intervention psychosociale artistique comme un moyen favorisant l’atteinte d’une justice sociale pour les groupes et populations marginalisés, précarisés ou oppressés. Pour ce faire, nous proposons d’abord un tour d’horizon théorique et posons quelques assises de l’intervention psychosociale artistique au Québec. Nous présentons ensuite trois objectifs d’intervention y étant associés : la prise de parole, l’acte réflexif et la prise de conscience des dimensions collectives des expériences individuelles. Par cet article, l’autrice et les auteurs désirent présenter les nombreux apports de ce type de pratique et en souligner le caractère novateur.
Keywords: OFDIG; approches et analyses; arts visuels et médiatiques; communication; discipline; intervention; marginalisation; privilèges; pédagogie; ressource en ligne; systèmes d'oppressions; thématiques

Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (ideas series, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics--one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie